FORMULATION OF CONCRETE BASED ON PLANT MATERIALS (CASE OF RICINODENDRON HEUDELOTII: AKPI): OPTIMIZATION OF THE PROPORTION OF SHELLS - MAMERY ADAMA SERIFOU; SOULEYMANE OUATTARA; BRAHIMAN TRAORE; CONAND HONORE KOUAKOU; EDJIKEME EMERUWA (Journal of Engineering Studies and Research)
The aims of this work is to study the influence of the partial substitution of natural aggregates by the nut shells of Ricinodendron heudelotii known as AKPI, on the physical-mechanical properties of concrete. The substitution rates made are 5%, 10% and 15%. Test results indicate that the presence of Akpi nut shells (ANS) causes increased porosity and reduced compressive strength of concrete. Increasing of porosity and decreasing of strength become important when the quantity of shell increases in concrete. However, the kinetics of hardening at a young age of the concrete is improved from 1% to 7%.